Previsión de los impactos ambientales negativos y el turismo urbano en la ciudad de Iquitos, 2021 - Alegria Baluarte, Maria Flavia (2023)
The thesis "Forecast of negative environmental impacts and urban tourism in the city of Iquitos, 2021", has the purpose of identifying the biotic and abiotic contaminants that interfere with the practice of good urban tourism. The study has been developed in the urban area of the city including the old town. The study has a quantitative and qualitative and cross-sectional approach with a descriptive design. Two data collection instruments were used, one for the Urban Tourism variable with indicators such as: buildings, events, landscapes and distractions, and another for the Environmental Pollution variable with closed questions regarding biotic and abiotic contamination observed in the city. The population were actors from the Environment and Tourism areas of the different institutions. The sample was non-probabilistic and the quantity was chosen for convenience, they were applied to the total of the environmental tourism and tourism actors of the government institutions of the city of Iquitos, which add up to 100. The hypothesis was proved, accepting that contamination Environmental is a negative option for the practice of urban tourism, since the pollutants are significant that prevent the good practice of urban tourism.